Henri La Barthe, l’inventeur de Détective - Dominique Kalifa (Criminocorpus)
The famous magazine Detective founded by Gallimard and the brothers Kessel was first a professional gazette created in 1925 by the private detective Henri La Barthe, who sold it to Gaston Gallimard three years later. This article highlights the unsung fate of “Detective Ashelbé” (HLB), who acquired an ephemeral notoriety when the film director Julien Duvivier adapted his novel Pépé le Moko. It illuminates the functioning of a small corporate sheet in the mediocre milieu of the 1920s French private police and traces the relationships that eventually link Ashelbé and Gallimard.